2011
DOI: 10.1007/s10554-011-9881-7
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of dual-energy CT to coronary CT angiography for the detection of significant coronary stenosis: comparison with quantitative coronary angiography and single photon emission computed tomography

Abstract: To determine the value of dual-energy CT (DECT) and combined information of perfusion and angiography in diagnosing coronary artery disease (CAD), with single photon emission computed tomography (SPECT) and quantitative coronary angiography (QCA) as a reference standard. Thirty-four patients were enrolled in this study. DECT was used as a contrast-enhanced retrospectively ECG-gated scan protocol during the rest state and tubes were set at 140/100 kV. DECT angiography (DE-CTA) and DECT perfusion (DE-CTP) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 32 publications
0
60
0
2
Order By: Relevance
“…Wang et al were among the first to evaluate the incremental value of CTP using DECT over CCTA among 34 patients with known CAD or abnormal SPECT (76). In this study, the combined assessment of CTP plus CCTA (with a sensitivity of 82% and specificity of 91%) achieved improved diagnostic performance compared to the individual use of CCTA or CTP with DECT.…”
Section: Combined Evaluation Ccta and Ctpmentioning
confidence: 78%
“…Wang et al were among the first to evaluate the incremental value of CTP using DECT over CCTA among 34 patients with known CAD or abnormal SPECT (76). In this study, the combined assessment of CTP plus CCTA (with a sensitivity of 82% and specificity of 91%) achieved improved diagnostic performance compared to the individual use of CCTA or CTP with DECT.…”
Section: Combined Evaluation Ccta and Ctpmentioning
confidence: 78%
“…Compared with the reference standard of SPECT, Wang et al 86 showed that sensitivity in, specificity of and accuracy of detecting coronary stenosis .50% by addition of DE FP CT increased from 82%, 91% and 86% with cCTA alone to 90%, 86% and 88%, respectively. 88 A recent trial of 50 patients comparing DE CT and SPECT for the detection of obstructive CAD against a gold standard of cMRI reported higher sensitivity (90% vs 85%) and specificity (71% vs 58%) with DE FP CT rather than SPECT (Figures 2 and 3). …”
Section: Dual Energy Ct Post-processing Techniquementioning
confidence: 94%
“…Clinical studies using dual energy first-pass CT Comparisons of DE FP CT to cMRI and PCI, 92 cMRI and SPECT, 53,85 as well as PCI and SPECT 88 have demonstrated its accuracy. Ko et al 92 found that DE FP CT could diagnose reversible ischaemia identified by cMRI with 89% sensitivity, 78% specificity and 82% accuracy.…”
Section: Dual Energy Ct Post-processing Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…As rest DECT-P is derived from the same datasets as standard cCTA, it requires no additional contrast media, radiation exposure, or stress agents, which represents a substantial advantage, when compared to stress protocols. Studies have compared DECT-P with single-photon emission computed tomography (SPECT), magnetic resonance imaging (MRI), and ICA in rest or rest-stress acquisition with first or second generation dual-source scanners and found an incremental value over cCTA alone (3)(4)(5)(6). However, the data for rest-only acquisition in DECT-P is rather sparse and needs further investigation regarding the clinical utility and its effect on patient care in a real clinical setting.…”
mentioning
confidence: 99%